Grinding aid composition for aggregate crushing process under hard water conditions
Patent Information
- Application Number
- KR1020260047689
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-03-17
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2046-03-17
Smart Images

Figure 112026032229998-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a crushing aid composition that can improve crushing efficiency while suppressing the aggregation of fine particles, scale formation, and caking phenomena that may occur when high-hardness water is used as the process water in a wet crushing process performed using process water in an aggregate crushing line. Background Technology
[0003] In general, in aggregate production processes for producing road aggregates, concrete aggregates, or construction aggregates, a crushing line consisting of jaw crushers, cone crushers, and impact crushers is used.
[0004] In these aggregate crushing lines, a wet crushing process using water is widely applied to suppress dust generated during the crushing process and to reduce equipment wear.
[0005] In particular, large-scale aggregate production facilities often use groundwater or recycled water as process water, and such process water contains calcium (Ca 2 + ) and magnesium (Mg 2 + It is often a high-hardness water containing a large amount of ions.
[0006] In such cases, when high-hardness water is used, the fine particles generated during the crushing process may react with the calcium components contained in the process water to form inorganic scale, such as calcium carbonate. This scale may adhere to the inside of the crushing equipment, transfer lines, or screen devices, thereby reducing the operational efficiency of the equipment.
[0007] In addition, a caking phenomenon may occur during the crushing process, where fine particles aggregate to form clumps. This caking can cause screen blinding or transfer line blockage, thereby reducing the processing capacity of the crushing line.
[0008] Meanwhile, during the process of crushing aggregates such as limestone or granite, a large amount of fine powder is generated. If these fine particles re-attach to the surface of the aggregate, the surface cleanliness of the aggregate may be reduced. In particular, when such aggregates are used in the manufacture of concrete, the interfacial adhesion between the aggregate and the cement paste is reduced, which may lead to problems such as a decrease in the compressive strength, durability, and crack resistance of the concrete.
[0009] Conventionally, some technologies using grinding aids containing dispersants or surfactants have been proposed to solve these problems; however, since conventional technologies mainly focus on improving the dispersibility of fine particles, they have limitations in effectively controlling scale formation and caking phenomena occurring in high-hardness water environments simultaneously.
[0010] Therefore, there is a need to develop a new grinding aid composition that can improve the surface cleanliness of aggregates while effectively suppressing scale formation, fine particle aggregation, and caking phenomena that occur when high-hardness water is used in the process of crushing aggregates such as limestone and granite. Prior art literature
[0012] Republic of Korea Patent Registration No. 10-222776 The problem to be solved
[0013] Accordingly, the present invention has been devised to solve the above-mentioned problems and aims to provide a grinding aid composition capable of improving grinding efficiency and the cleanliness of the aggregate surface while effectively suppressing the aggregation of fine particles, scale formation, and caking phenomena that may occur during the aggregate crushing process in a high-hardness water environment. means of solving the problem
[0015] To achieve the above objective, the grinding aid composition for an aggregate crushing process in a high-hardness water environment according to the present invention (hereinafter referred to as "the composition of the present invention") is characterized by comprising, for every 100 parts by weight of a polycarboxylate-based material, 30 to 80 parts by weight of aminotrimethylene phosphate, 20 to 40 parts by weight of an acrylic acid-maleic acid copolymer, 3 to 10 parts by weight of an EO-PO block copolymer, 50 to 150 parts by weight of water, 3 to 8 parts by weight of a lignin sulfonate, 1 to 5 parts by weight of SAP, and 0.5 to 2 parts by weight of octyl palmitate.
[0016] As an example, it is characterized by further including 0.1 to 1 weight part of magnesium carbonate.
[0017] delete
[0018] delete
[0019] delete
[0020] As an example, it is characterized by further including 1 to 5 parts by weight of hyaluronic acid.
[0021] As an example, it is characterized by further including 0.5 to 2 parts by weight of calcium formate. Effects of the invention
[0023] According to the composition of the present invention, the formation of inorganic scale that may occur in a high-hardness water environment can be effectively suppressed, the aggregation and caking phenomena of fine particles occurring in the wet crushing process can be suppressed, the cleanliness of the aggregate surface can be improved by suppressing the re-attachment of fine powder to the aggregate surface during the grinding process, and the interfacial adhesion between the aggregate and the cement paste can be improved, thereby improving physical properties such as the compressive strength of the concrete. Brief explanation of the drawing
[0025] Figures 1 to 4 are photographs showing the composition of the present invention. Specific details for implementing the invention
[0026] Hereinafter, the structure and operation of the present invention will be explained in more detail with reference to the attached drawings. In describing the present invention, terms and words used in this specification and claims must be interpreted in a meaning and concept consistent with the technical spirit of the present invention, based on the principle that the inventor can appropriately define the concept of the terms to describe his invention in the best way possible.
[0028] The composition of the present invention is characterized by comprising 30 to 80 parts by weight of aminotrimethylene phosphate (ATMP), 20 to 40 parts by weight of an acrylic acid-maleic acid copolymer, 3 to 10 parts by weight of an EO-PO block copolymer, and 50 to 150 parts by weight of water, based on 100 parts by weight of a polycarboxylate-based compound.
[0029] Polycarboxylates act as the primary dispersion component of grinding aids and prevent fine particles generated during the aggregate crushing process from aggregating. Polycarboxylate polymers contain carboxyl groups (-COO) within their molecular structure. - It adsorbs to the particle surface and simultaneously imparts electrostatic repulsion and steric hindrance. As a result, aggregation between fine particles is suppressed, which improves grinding efficiency and reduces the phenomenon of fine powder reattaching to the aggregate surface.
[0030] Polycarboxylate-based materials such as polycarboxylate ethers, polycarboxylate copolymers, and methacrylic acid-based polycarboxylates may be applied.
[0031] The above ATMP is a phosphate-based chelate / scale inhibitory component, and Ca present in high-hardness water 2+ , Mg 2 + It interacts with metal ions such as the like to inhibit the nucleation and crystal growth of inorganic scale, and mitigates the attachment and accumulation of scale on the inner walls of the facility or screen devices.
[0032] In addition, as the scale is mitigated, screen clogging and fine particle reattachment are reduced, which can improve process stability.
[0033] If the above ATMP is less than 30 parts by weight, the scale control effect under high hardness water conditions may not be sufficiently expressed, and if it exceeds 80 parts by weight, process stability or economic efficiency may decrease due to increased acidity / ionicity of the composition, so it is desirable to limit it to the above range.
[0034] The above acrylic acid-maleic acid copolymer (AA-MA) is a polycarboxyl group-based polymer dispersant that inhibits the aggregation of fine particles and prevents the fine particles from reattaching to the aggregate surface by adsorbing to the surface of fine particles and providing electrical repulsion and steric hindrance effects.
[0035] Especially in high-hardness water environments, Ca 2 + By maintaining dispersibility even under conditions where fine particle aggregation is promoted, it contributes to mitigating screen clogging and reduced grinding efficiency that may occur due to scale / caking.
[0036] If the above AA-MA is less than 20 parts by weight, the dispersion stability may be insufficient, and if it exceeds 40 parts by weight, the process fluidity may be reduced due to excessive dispersion / viscosity increase, so it is desirable to limit it to the above range.
[0037] The above EO-PO block copolymer is a component that provides nonionic surfactant function, improves wettability on raw stone / aggregate surfaces and fine particles, and assists in particle dispersion in the slurry to alleviate aggregation and caking.
[0038] If the above EO-PO block copolymer is less than 3 parts by weight, the wetting and dispersion assisting effects may not be sufficient, and if it exceeds 10 parts by weight, process stability may be compromised due to excessive bubble stabilization or changes in process viscosity, so it is desirable to adopt the above range.
[0039] The above water serves as a solvent to uniformly mix each component and prepare a liquid composition. In the present invention, considering the viscosity and handling properties of the composition, it is preferable to use 50 to 150 parts by weight per 100 parts by weight of the polycarboxylate-based water.
[0040] In addition, the composition of the present invention may further include lignosulfonate.
[0041] Lignin sulfonates are anionic polymers produced by sulfonating woody lignin, and are designed to perform a dispersion function while simultaneously inhibiting the formation of inorganic scale through interaction with metal ions.
[0042] In the aggregate crushing process, scale may form on the equipment and the surface of fine particles due to calcium components in the process water. This scale can induce the aggregation of fine particles and cause them to re-attach to the aggregate surface. Consequently, the cleanliness of the aggregate surface deteriorates, and the interfacial adhesion between the aggregate and the cement paste decreases, which can lead to a reduction in the compressive strength and crack resistance of the concrete.
[0043] Accordingly, in the present invention, by adding lignin sulfonate, scale formation is suppressed and the dispersibility of fine particles is improved, thereby improving the cleanliness of the aggregate surface. Consequently, the interfacial adhesion between the aggregate and the cement paste is enhanced, which can improve the compressive strength and crack resistance of the concrete.
[0044] Preferably, the lignin sulfonate is appropriately formulated in a range of 3 to 8 parts by weight per 100 parts by weight of the polycarboxylate system.
[0045] On the other hand, when only lignin sulfonates are added, the cement hydration reaction is partially delayed, which may increase the time the concrete remains in the plastic state; consequently, if surface moisture evaporation continues in this state, there is a problem that the likelihood of plastic shrinkage cracks occurring increases.
[0046] Accordingly, the present invention provides an example in which SAP (Super Absorbent Polymer) is further included.
[0047] SAP can provide an internal curing effect by storing moisture internally and releasing it when the moisture content of the concrete decreases; consequently, it can suppress plastic shrinkage by reducing capillary tension. Furthermore, SAP can reduce crack formation by stabilizing the internal moisture distribution of the concrete and inhibiting self-desiccation.
[0048] Preferably, it is appropriate to incorporate 1 to 5 parts by weight of SAP per 100 parts by weight of polycarboxylate-based.
[0049] In addition to this, the present invention provides an example in which octyl palmitate is further included in addition to lignin sulfonate and SAP.
[0050] Octyl palmitate is a long-chain fatty acid ester compound that performs the function of reducing surface tension and improving the wettability of fine particles and aggregate surfaces.
[0051] While the aforementioned SAP provides an internal curing effect by controlling moisture inside the concrete, octyl palmitate can play a role in mitigating the rate of moisture evaporation from the concrete surface.
[0052] In other words, while SAP performs the function of inhibiting moisture loss within the concrete, octyl palmitate performs the function of inhibiting moisture evaporation from the concrete surface, allowing the two materials to act complementarily.
[0053] In this way, when internal moisture retention and surface moisture retention are achieved simultaneously, plastic shrinkage of concrete can be suppressed more effectively, and consequently, resistance to plastic shrinkage cracking can be further improved.
[0054] Preferably, octyl palmitate is appropriately formulated in an amount of 0.5 to 2 parts by weight per 100 parts by weight of polycarboxylate-based.
[0055] Meanwhile, the addition of SAP can cause fine particles that have absorbed moisture to aggregate, leading to caking. This caking causes the fine particles to re-attach to the aggregate surface, which can reduce the interfacial adhesion between the aggregate and the cement paste. Consequently, the compressive strength of the concrete may decrease.
[0056] Accordingly, the present invention provides an example in which magnesium carbonate is added to improve the flowability of the powder and suppress aggregation between particles, thereby effectively controlling caking. In other words, the compressive strength of the concrete is further enhanced through the control of caking by the addition of magnesium carbonate.
[0057] Preferably, magnesium carbonate is appropriately formulated in an amount of 0.1 to 1 weight part per 100 weight parts of the polycarboxylate-based material.
[0058] Meanwhile, as previously mentioned in the present invention, scale formation that may occur during the aggregate crushing process can be suppressed to a certain level by the action of the polycarboxylate-based, aminotrimethylene phosphate and acrylic acid maleic acid copolymer.
[0059] However, depending on process conditions, scale formation may not be completely controlled, which may cause fine particles to remain on or reattach to the aggregate surface, thereby reducing interfacial adhesion between the aggregate and the cement paste.
[0060] Accordingly, the present invention provides an example in which hyaluronic acid is additionally included to improve the interaction between the aggregate surface and cement paste particles and to increase interfacial bonding strength, thereby effectively compensating for the problem of reduced interfacial adhesion that may occur due to residual scale.
[0061] Hyaluronic acid is a high-molecular-weight polysaccharide containing multiple carboxyl and hydroxyl groups, possessing excellent water affinity and the ability to adsorb onto the surfaces of various inorganic particles. This hyaluronic acid adsorbs onto the aggregate surface and the constituent particles of the cement paste to form a thin, water-friendly polymer layer, thereby playing a role in improving the interfacial bonding strength between the aggregate and the cement paste.
[0062] Accordingly, the interface transition zone (ITZ) between aggregate and cement paste can be formed more stably during concrete manufacturing, and as a result, contributes to improving the compressive strength of the concrete.
[0063] Preferably, hyaluronic acid is appropriately formulated in an amount of 1 to 5 parts by weight per 100 parts by weight of polycarboxylate-based.
[0064] On the other hand, when polymeric materials such as hyaluronic acid are added, the hydration reaction may be partially delayed by the polymer layer adsorbed on the surface of cement particles, which may lead to a problem of reduced early strength development of the concrete.
[0065] Accordingly, the present invention provides an example in which calcium formate is further added. By including the calcium formate, the initial hydration delay that may occur due to the addition of hyaluronic acid can be compensated for, thereby preventing a decrease in the initial strength of the concrete.
[0066] Preferably, the calcium formate is appropriately formulated in a range of 0.5 to 2 parts by weight per 100 parts by weight of the polycarboxylate-based.
[0068] Embodiments of the present invention will be explained through the following experimental examples.
[0069] First, raw limestone brought in from a quarry was prepared for the experiment. The prepared limestone was sifted to have a particle size ranging from approximately 25 mm to 60 mm, and a sifting process was performed to remove wood, soil, and other foreign substances. In this experiment, high-hardness water containing calcium and magnesium ions was used as the process water to simulate the conditions of the actual aggregate production process, and the total hardness of the process water was CaCO3 It was adjusted to a level of approximately 250±20 mg / L based on the conversion standard.
[0070] A wet crushing process was performed on the limestone prepared in this manner. The crushing process was carried out by sequentially performing primary crushing with a jaw crusher and secondary crushing with a cone crusher, followed by classification through a screen.
[0071] In the crushing process, process water was sprayed to maintain wet conditions in order to suppress dust generation and simulate the operating conditions of an actual aggregate crushing line. The crushing aid was introduced through the process water line and injected to achieve a solid content concentration of approximately 300 ppm (0.03 wt%) based on the raw material processing volume. Meanwhile, in the comparative example, the experiment was conducted under the same process conditions without introducing the crushing aid.
[0072] The evaluation of grinding efficiency was performed by comprehensively considering factors such as the amount of fine powder generated during the crushing process and the degree of screen clogging.
[0073] Specifically, aggregates were collected before and after the crushing process and subjected to sieve analysis, and the amount of fine particles of 0.075 mm or less was measured. In addition, the material adhering to the screen during the crushing process was recovered after a certain period of operation, dried, and the amount of screen clogging was measured. Meanwhile, the power consumption required for the crushing process was measured and divided by the weight of the treated limestone to calculate the unit energy (kWh / t).
[0074] In this manner, a limestone crushing process was performed by applying the crushing aid of each example below, and the results are presented in Table 1.
[0076] <Example 1>
[0077] 50 parts by weight of aminotrimethylene phosphate, 30 parts by weight of acrylic acid maleic acid copolymer, 10 parts by weight of EO-PO block copolymer, and 130 parts by weight of water were mixed with 100 parts by weight of a polycarboxylate-based mixture.
[0079] <Example 2>
[0080] It was identical to Example 1, except that 4 parts by weight of lignin sulfonate were added.
[0082] <Example 3>
[0083] It is identical to Example 2, but with an additional 2 parts by weight of SAP added.
[0085] <Example 4>
[0086] It was identical to Example 3, except that 1 weight part of octyl palmitate was added.
[0088] <Example 5>
[0089] It was the same as Example 4, but with an additional 0.3 parts by weight of magnesium carbonate added.
[0091] <Example 6>
[0092] It was identical to Example 1, except that 3 parts by weight of hyaluronic acid were added.
[0094] <Example 7>
[0095] It was the same as Example 6, except that 0.5 parts by weight of calcium formate were added.
[0097] division Unit energy (kWh / t) 0.075mm Generation Amount (%) Screen clogging amount (g) Comparative example 2.35 7.6 520 Example 1 2.05 6.3 360 Example 2 1.98 6.1 280 Example 3 2.02 6.0 370 Example 4 1.96 6.0 365 Example 5 1.90 5.9 220 Example 6 2.03 6.2 335 Example 7 2.02 6.2 330
[0099] Looking at Table 1 above, it can be seen that compared to the comparative example, the examples show a tendency for reduced unit energy consumption, maintained fine particle content at an appropriate level, and reduced screen clogging. This is believed to be because the dispersibility of fine particles is improved and caking formation is suppressed by the action of the grinding aid.
[0100] When comparing Example 1 and Example 2, it can be seen that the amount of screen clogging is reduced in the case of Example 2, which is believed to be because scale formation during the process is suppressed and the aggregation of fine particles is reduced by the addition of ligninsulfonate in Example 2.
[0101] When comparing Example 2 and Example 3, it can be seen that Example 3 shows a tendency for screen clogging to increase, which is believed to be because fine particles that absorbed moisture due to the addition of SAP aggregated together, causing some increase in caking.
[0102] Meanwhile, when comparing Example 3 and Example 5, it can be seen that the amount of screen clogging in Example 5 is significantly reduced. This is believed to be because the formation of caking was suppressed as physical gaps between particles were formed due to the additional inclusion of magnesium carbonate in Example 5.
[0103] Therefore, from the above results, it is confirmed that in the case of Example 5 containing magnesium carbonate, caking formation is effectively suppressed during the grinding process, resulting in the best grinding efficiency.
[0104] Next, samples were prepared according to the formulation in Table 2 below, and flow (KS F 2594), compressive strength (KS F 2405), and crack resistance (KS F 2424, 28 days) were tested, and the results are shown in Table 3.
[0106] division W / C Air volume (%) OPC(kg / m³) S(㎏ / ㎥) G(㎏ / ㎥) W(㎏ / ㎥) combination 0.50 4.5±1.0 320 728 1,060 160
[0107] S: Natural sand, G: Aggregate manufactured according to each example
[0109] division FLOW(mm, 30 min) Rate of change in length (X 10 -6 ) Compressive strength (MPa) 1 day 3 days 7 days 28th Example 1 175 / 160 -580 16 26 33 41 Example 2 178 / 162 -565 16 27 34 42 Example 3 180 / 169 -500 15 26 33 41 Example 4 183 / 170 -480 15 26 33 42 Example 5 182 / 171 -470 16 27 34 44 Example 6 170 / 154 -570 14 25 34 44 Example 7 172 / 156 -580 16 27 35 44
[0111] Looking at Table 3 above, it can be seen that Examples 1 to 7 all exhibit relatively good flow values. This is attributed to the fact that fine particles attached to the surface of the aggregate are effectively removed by the action of the grinding aid, and the cleanliness of the aggregate surface is improved, thereby improving the fluidity of the concrete.
[0112] When comparing Example 1 and Example 2, it can be seen that the flow value in Example 2 tends to increase slightly. This is because the addition of lignin sulfonate improves the dispersibility of fine particles and partially suppresses scale formation on the aggregate surface, thereby improving the workability of the concrete.
[0113] When comparing Example 2 and Example 3, it can be seen that Example 3 shows a tendency for flow retention to improve somewhat, which is believed to be because the moisture distribution inside the concrete is stabilized and moisture loss is partially suppressed by the addition of SAP.
[0114] When comparing Example 3 and Example 4, it can be seen that the flow value in Example 4 shows a tendency to increase slightly, which is attributed to the addition of octyl palmitate improving the wettability of the aggregate and fine powder surfaces, thereby improving the fluidity of the concrete.
[0115] Meanwhile, when comparing Example 1 and Example 6, it can be seen that the flow value in Example 6 tends to decrease slightly, which is believed to be due to the increase in viscosity of the concrete mixture caused by the addition of hyaluronic acid.
[0116] When comparing Example 6 and Example 7, it can be seen that the flow value of Example 7 remains at a level similar to that of Example 6. This is believed to be because the relatively small amount of calcium formate added does not significantly affect the fluidity of the concrete mixture.
[0117] When comparing Example 1 and Example 2 in terms of crack resistance, it can be seen that Example 2 shows a tendency for the rate of change in length to decrease slightly. This is believed to be because the addition of lignin sulfonate inhibits scale formation on the aggregate surface and improves interfacial adhesion between the aggregate and the cement paste.
[0118] When comparing Example 2 and Example 3, it can be seen that the rate of change in length is significantly reduced in the case of Example 3. This is believed to be because the moisture stored inside the concrete is gradually released due to the addition of SAP, thereby exhibiting an internal curing effect.
[0119] When comparing Example 3 and Example 4, it can be seen that the rate of change in length is further reduced in the case of Example 4. This is believed to be because the addition of octyl palmitate partially suppresses moisture evaporation from the concrete surface, thereby further reducing drying shrinkage.
[0120] When comparing Example 4 and Example 5, it can be seen that Example 5 exhibits the smallest value for the rate of change in length. This is believed to be because the addition of magnesium carbonate suppresses caking and maintains a uniform aggregate surface condition, thereby forming a more stable internal structure of the concrete.
[0121] When comparing Example 1 and Example 2 in terms of compressive strength, it can be seen that Example 2 shows a tendency for slightly increased compressive strength. This is believed to be because the addition of lignin sulfonate suppresses scale formation on the aggregate surface and reduces the aggregation of fine particles, thereby forming a more stable interfacial bond between the aggregate and the cement paste.
[0122] When comparing Example 3 and Example 5, it can be seen that Example 5 exhibits the highest compressive strength value. This is believed to be because the addition of magnesium carbonate suppresses caking, resulting in a more uniform aggregate surface condition during the grinding process, and consequently, a more dense internal concrete structure.
[0123] Meanwhile, when comparing Example 1 and Example 6, it can be observed that in the case of Example 6, the compressive strength (1 day, 3 days) tends to decrease slightly at the initial age. This is believed to be because the addition of hyaluronic acid caused a polymer layer to form on the surface of the cement particles, thereby partially delaying the initial hydration reaction. On the other hand, it can be observed that the compressive strength of Example 6 tends to increase as the age increases (7 days, 28 days). This is believed to be because hyaluronic acid improved the interfacial bonding strength between the aggregate and the cement paste, thereby forming a more dense internal structure of the concrete.
[0124] When comparing Example 6 and Example 7, it can be seen that the initial compressive strength of Example 7 increased compared to Example 6. This is believed to be because the hydration reaction of the cement was promoted by the addition of calcium formate, thereby improving the development of the initial strength.
[0126] From the above description, those skilled in the art will understand that various changes and modifications are possible within the scope of the technical concept of the present invention. Accordingly, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification, but should be determined by the claims.
Claims
Claim 1 A grinding aid composition for an aggregate crushing process in a high-hardness water environment, characterized by comprising, per 100 parts by weight of a polycarboxylate-based material, 30 to 80 parts by weight of aminotrimethylene phosphate, 20 to 40 parts by weight of an acrylic acid-maleic acid copolymer, 3 to 10 parts by weight of an EO-PO block copolymer, 50 to 150 parts by weight of water, 3 to 8 parts by weight of lignin sulfonate, 1 to 5 parts by weight of SAP, and 0.5 to 2 parts by weight of octyl palmitate. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 A grinding aid composition for an aggregate crushing process in a high-hardness water environment, characterized in that, in claim 1, it further comprises 0.1 to 1 weight part of magnesium carbonate. Claim 6 A grinding aid composition for an aggregate crushing process in a high-hardness water environment, characterized in that, in claim 1, it further comprises 1 to 5 parts by weight of hyaluronic acid. Claim 7 A grinding aid composition for an aggregate crushing process in a high-hardness water environment, characterized in that, in claim 6, it further comprises 0.5 to 2 parts by weight of calcium formate.
Citation Information
Patent Citations
Corrosion-resistant pigment and a composition incorporating the pigment
KR1019990044121A
Maufacturing methode of loess mortar
KR1020050077452A
A Grinding aid
KR1020180050852A
Ultra High Density Concrete, Manufacturing Method of such Concrete, Concrete Member made by such Concrete, and Manufacturing Method of such Concrete Member
KR102255042B1
Wet press concrete slab manufacturing
WO2016081080A1
